Science and technology policy in the process of industrialization of the country: Experiences from some countries and the current situation in Vietnam - Nguyen Hoang Hai; Tran Thi Kim Oanh; Tran Hai Minh; Dang Thu Minh; Dang Thi Thu Trang (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2025)
The studies on the process of promoting industrialization of countries in the East Asian region all have the same opinion about the role and contribution of science and technology (S&T) policy in accelerating the process of catching up with the industrialized countries, not only in terms of products, goods, services but also in improving the capacity and level of national S&T. Vietnam's S&T policy in recent years has also been oriented to contribute to the process of industrialization of the country. Although Vietnam's S&T policy system has had certain positive impacts on the country's development process, there are still certain barriers and challenges. This article provides some comparisons between S&T policy in the industrialization process of 03 countries (Japan, Korea, China) and Vietnam's S&T policy in recent times, thereby proposing some suggestions to improve the policy in the coming time. Code: 24040501